Uma investigação sobre o uso da informação na cadeia interna de suprimentos em hospitais na cidade de São Paulo - Paes, Libânia Rangel de Alvarenga (2009)
The interest in research on how information technology helps the internal management of hospital supplies arose due to the wide participation of inputs in hospital costs (15 to 30%) and little attention given to the analysis of the internal chain of hospitals and their relationship with technology . This research includes their control and tracking, since its entry into the hospitals to their use in procedures in patients. The choice of the subjects, Information Technology and Supply Chain Management, was based on research in the area of Information Systems and the analysis of these two areas in hospital organizations, focusing on the internal processes of distribution, is scarce. The contribution of this work is the evaluation of hospitals facing the already established models and structures used by companies in other segments and in the areas of manufacturing and services. The survey results, based on interviews with managers and supply of information technology in five hospitals of São Paulo, showed that domestic supplies hospital chains have characteristics of both products and services companies. The coexistence of these features, however, is an advantage for organizations, as they can assimilate the experience of both models, only adjusting them for different phases of internal distribution. Information systems that support the chains require, however, greater integration with data services to be more efficient.